2009
DOI: 10.1042/bsr20080123
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of VDAC2 purified from mammal spermatozoa

Abstract: VDAC (voltage-dependent anion channel) is the pore-forming protein located in the outer mitochondrial membrane. In higher eukaryotes, three genes encode VDAC. Nevertheless, the knowledge of VDAC isoforms is mainly restricted to VDAC1, the only isoform that has been characterized from living tissues to date. We have highly enriched the isoform VDAC2 using as starting material bovine spermatozoa. VDAC2 was obtained in the hydroxyapatite/celite pass-through of sperm proteins solubilized with Triton X-100. This fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…This suggests that cytoplasmic translation in sperm may be regulated by lysine acetylation. Because of the successful enrichment of lysine-acetylated peptides, we were able to identify novel VDACs, one of which was recently characterized in both bovine and human sperm (50,52). Modification of channel proteins by acetylation is virtually unexplored territory except for a recent report in which incretin regulates ␤-cell function via the acetylation of multiple Kv␣ and Kv␤ subunits (59).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that cytoplasmic translation in sperm may be regulated by lysine acetylation. Because of the successful enrichment of lysine-acetylated peptides, we were able to identify novel VDACs, one of which was recently characterized in both bovine and human sperm (50,52). Modification of channel proteins by acetylation is virtually unexplored territory except for a recent report in which incretin regulates ␤-cell function via the acetylation of multiple Kv␣ and Kv␤ subunits (59).…”
Section: Discussionmentioning
confidence: 99%
“…Triton X-100 extracts of whole spermatozoa were applied to HTP/Celite, yielding an eluate containing VDAC2 and traces of VDAC3 and VDAC1 (Menzel et al, 2009). The various purification procedures described above have permitted VDAC purification from numerous tissues and organisms (for review, see (Benz, 1994)).…”
Section: The Vdac Proteinmentioning
confidence: 99%
“…Few recent studies have reported that VDAC is present in mammalian spermatozoa and plays putative roles in spermatogenesis, sperm maturation and fertilization [15][16][17][18][19]. However the respective expression, localization and function of three VDAC subtypes remain uncertain.…”
Section: Introductionmentioning
confidence: 99%